2017
DOI: 10.1371/journal.pone.0183602
|View full text |Cite
|
Sign up to set email alerts
|

Benzene exposure is associated with cardiovascular disease risk

Abstract: Benzene is a ubiquitous, volatile pollutant present at high concentrations in toxins (e.g. tobacco smoke) known to increase cardiovascular disease (CVD) risk. Despite its prevalence, the cardiovascular effects of benzene have rarely been studied. Hence, we examined whether exposure to benzene is associated with increased CVD risk. The effects of benzene exposure in mice were assessed by direct inhalation, while the effects of benzene exposure in humans was assessed in 210 individuals with mild to high CVD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 40 publications
2
51
2
Order By: Relevance
“…Various sources of benzene exposure include drinking contaminated water or food, smoking cigarettes, breathing secondhand cigarette smoke, vehicle exhaust or petroleum fuels, vaping e-cigarettes, using paint or detergent products [6][7][8][9][10][11][12][13][14]. While values of ambient benzene air concentrations in the U.S. have typically been <1 ppm (parts per million), significantly higher levels can be experienced as a result of various environmental factors [15] [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various sources of benzene exposure include drinking contaminated water or food, smoking cigarettes, breathing secondhand cigarette smoke, vehicle exhaust or petroleum fuels, vaping e-cigarettes, using paint or detergent products [6][7][8][9][10][11][12][13][14]. While values of ambient benzene air concentrations in the U.S. have typically been <1 ppm (parts per million), significantly higher levels can be experienced as a result of various environmental factors [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated an association between levels of urinary benzene metabolites in elderly adults living in polluted areas and insulin resistance (IR) [23]. Additionally, benzene exposure and presence of urinary benzene metabolites are associated with increased cardiovascular risk and dyslipidemia in both smokers and nonsmokers, suggesting that benzene may be linked to cardiovascular injury, even in the absence of exposure to other tobacco smoke constituents [16]. Benzene exposure during pregnancy is strongly associated with gestational diabetes among women belonging to underrepresented minorities in the US [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the effect of VC exposure on existing comorbidities, such as liver disease, is largely unknown 8 . This knowledge gap is especially important today due to the increasing global prevalence of nonalcoholic fatty liver disease (NALFD) 4,6,7,9,10,11,12 . Importantly, VC has recently been shown to be an independent risk factor for liver disease from other causes 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Benzene is known to be carcinogenic at high concentrations, but its association in causing metabolic diseases particularly T2DM is still emerging. Recent studies demonstrated that benzene non-cancerous health effects at environmental levels include impaired glucose homeostasis and insulin resistance (Abplanalp et al 2017;Amin et al 2018;Debarba et al 2020). We have recently shown that chronic exposure of adult mice to benzene at the levels relevant to human exposures associated with cigarette smoke (50 ppm) induces severe metabolic imbalance associated with central hypothalamic inflammation and endoplasmic reticulum (ER) stress in a sex-specific manner (Debarba et al 2020).…”
Section: Introductionmentioning
confidence: 99%